Transformasi Digital dalam Pendidikan Serta Penggunaan Teknologi Komunikasi oleh Mahasiswa - Ahmad Holidin; Haryanto Haryanto; Andri Cahyo Purnomo (Journal of Science, Technology, and Innovation, 2025)
This study examines digital transformation in higher education through the lens of university students’ use of communication technologies in learning contexts. Focusing on expectation confirmation, actual usage, and satisfaction, the findings reveal that students generally perceive communication technologies as meeting their performance expectations, particularly email systems and instant messaging platforms. Email emerges as the most dominant technology, demonstrating the highest levels of confirmation, frequent use, and satisfaction, indicating its continued relevance as a stable and formal academic communication medium. Instant messaging also shows strong acceptance, reflecting students’ preference for rapid and flexible interaction. In contrast, video conferencing systems, social media, and collaborative technologies exhibit lower levels of regular use and satisfaction, accompanied by substantial neutral responses, suggesting partial integration into academic practices. These patterns indicate that while digital transformation has advanced, its implementation remains uneven across different types of communication technologies.